Transfer Gen Penanda Pada Kentang (Solanum tuberosum L.) CV Panda dan Atlantik dengan Bantuan Agrobacterium - Noor Aini Habibah; Sri Nanan B (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2005)
This research was carried out to evaluate the efficiency of marker gene transfer of potato (Solanum tuberosum L.) explant tissues, which were co-cultivated with Agrobacterium tumefaciens strain LBA 4404 carrying binary vector pBI121. Nodes and leaf segments from shoot cultures of Panda and Atlantic cultivars were used as explants. The marker gene transfer procedure was initiated with explant pre-conditioning, followed with co-cultivating and selecting of putative transformant cells. Explants were pre-conditioned over-night in callus induction medium containing basal medium of MS (Murashige & Skoog, 1962) supplemented with 5 mg/l naphthalene acetic acid (NAA) and 0.1 mg/l benzyl adenine. After 10 min. inoculation in  A. tumefaciens suspension, explants were co-cultivated for 1, 3, 5, 7 and 9 days. After co-cultivation, explant tissues were placed on callus induction medium added with 150 mg/l kanamycin. Successful marker gene transfer was calculated as the percentage of total explants producing callus on selection medium. Results showed that more co-cultivated nodal explants became resistant to kanamycin than co-cultivated leaf explants. The highest efficiency of transformation (45%) of nodal explants was observed in Panda cultivar whereas that in Atlantik was only 30%. The most efficient transformation of leaf explants was observed in Panda cultivar (20%) whereas that in Atlantik was15%. The PCR analysis detected the presence of NPTII gene in transgenic tissues.